Step by Step Into Adulthood: Predictors of Psychological Maturity in Adolescents - Eryilmaz, Ali; Basar-Gencer, Dusum (WILEY, 2026)
Background: Psychological maturity represents the evolution of meaning-making systems from impulsive to self-authoring minds. In the Turkish cultural context, understanding how internal regulatory mechanisms and paternal influences foster this developmental transition is crucial for adolescent mental health. Methods: This correlational study included 271 high school students in Istanbul, T & uuml;rkiye. Data were collected using the Psychological Maturity Scale, Adolescent-Parent Conflict Scale, Emotion Regulation Scale, and Positive Father Scale. Multiple linear regression was employed to analyze relationships. Results: The regression model was statistically significant (F(3, 267) = 22.33, p < 0.001), explaining 20.1% of the variance in psychological maturity. Internal functional emotion regulation emerged as the strongest predictor (beta = 0.326, p < 0.001), followed by adolescent-parent conflict (beta = -0.197, p = 0.001) and positive father (beta = 0.131, p = 0.020). Findings: Psychological maturity is an interactive process where internal regulation serves as the important developmental architecture. While paternal support and internal regulation function as independent pathways to maturity, positive fathering provides a vital secure base that buffers the negative impact of conflict. Clinical interventions should prioritize both paternal engagement and adolescent regulatory skills to facilitate the transition to adult-level maturity.
Keywords: adolescent-parent conflict; emotion regulation; positive father; psychological maturity; DECISION-MAKING; CHILDHOOD; SELF; INVOLVEMENT; INTIMACY; EMPATHY; Nursing